К изучению гельминтофауны рыб семейства ящероголовых (Synodontidae) из Индийского океана - Парухин, А.М. (Вестник зоологии, 1974)
Helminthofauna characteristic is given for five fish species- Saurida undosquamis, S. tumbil, S. gracilis, Synodus variegatus, Trachinocephalus myops. Species composition of helminths parazitizing in them is different, which is explained by difference in ecology and nutrient relation of the above-mentioned fish genera. Extensity and intensity of the fish invasion depend on fish age.